A STUDY OF THE CLINICAL PROFILE OF PATIENTS HAVING CLEFT LIP AND PALATE - Dr. Jyoti Dvivedi; Dr. Sanjay Dvivedi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Cleft deformities are a challenge to the surgeons since very long. The present study was undertaken at a tertiary medical care centre in Dehradun, Uttarakhand keeping in mind the scarcity of such studies in this region. In this study 312 patients of cleft lip or cleft palate or both cleft lip and palate, were evaluated over a period of 12 months. The authors investigated the differences between age and sex with cleft status and family history of clefts, type of clefts, surgical procedures done on them; follow up in such children and patient/family satisfaction after treatment. Maximum numbers of patients were in the age group of 1–10 years and the incidence of clefts was higher in males. Bilateral clefts were present in 19.26% cases where as 50.37% cases had left sided clefts, 30.37% cases had right sided clefts. In the study sample maximum numbers of patients of cleft lip were treated by Randall–Tennison’s technique in almost 70% cases, while almost all the cleft palate patients were operated by Pushback technique. 6 cases showed over or under correction of the lip, 5 cases showed contracted scars but more than 90% of the families were fully satisfied by the treatment and results. This study will provide baseline information on the status of cleft patients in this state of Uttarakhand for future reference to health workers